2004
DOI: 10.1027/1015-5759.20.1.49
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Multi-Item Likert and Visual Analogue Scales for the Assessment of Transactionally Defined Coping Function1

Abstract: Summary: The evaluation and monitoring of interventions that are designed to alleviate psychosocial stress rely largely on subjective assessments of coping as primary outcome measures. The pros and cons of different response formats used to measure coping variables are unexplored; yet arguably, response format is a very important methodological issue for the clinical application and evaluation of psychosocial interventions. This study compared the levels of functional coping and transactional coping patterns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 28 publications
3
86
1
3
Order By: Relevance
“…A recent comparison of on-line Likert-type and visual analogue items used to measure functional coping (Flynn, van Schaik, & van Wersch, 2004), found consistently higher responses from the Likert-type scales. In this study, sets of Likert-type items with defined points on the rating scale were compared with exactly the same item content presented by visual analogue in the form of a continuous bar.…”
Section: Validity Of Single-item Measures Of Self-regulated Learning mentioning
confidence: 97%
“…A recent comparison of on-line Likert-type and visual analogue items used to measure functional coping (Flynn, van Schaik, & van Wersch, 2004), found consistently higher responses from the Likert-type scales. In this study, sets of Likert-type items with defined points on the rating scale were compared with exactly the same item content presented by visual analogue in the form of a continuous bar.…”
Section: Validity Of Single-item Measures Of Self-regulated Learning mentioning
confidence: 97%
“…With computer aided technology, respondents can freely specify the exact position of their response which can subsequently be quantified up to the pixel With Likert scales, respondents are limited to only certain categories on the continuum (Flynn, 2004). The increased sensitivity has been reported by researchers.…”
Section: Reasons To Use the Vas As Opposed To The Likert Scalementioning
confidence: 99%
“…Likert scales make the respondent specify his or her experience by selecting one graduated category from the many category options, with Likert scales usually containing four to eleven categories (Flynn, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Stubbs et al (2000) describe VAS scales as "easy and quick to use, simple to interpret, they do not require the subject to invoke their own descriptive terms, they allow considerable discrimination and they are presented in a standardized format" (Stubbs et al, 2000, p. 407). Other authors, however, argue that respondents need more training for VAS scales compared to LIK items, that changes and distances, especially in clinical and diagnostical research, are difficult to interpret and that no evidence can be found that VAS scales provide more reliable or more valid measures (Brunier & Graydon, 1996;Flynn et al, 2004;McKelvie, 1978). Apart from general considerations about the measurement quality of VAS scales, however, the continuous type of response could possibly reduce effects of social desirability and support self-disclosure in a specific way.…”
mentioning
confidence: 99%
“…The answers are usually coded in millimeters from the origin. VAS scales are considered to be especially preferred by respondents when their intended answers do not fit with the categories of LIK items (Flynn, Schaik, & Wersch, 2004). Stubbs et al (2000) describe VAS scales as "easy and quick to use, simple to interpret, they do not require the subject to invoke their own descriptive terms, they allow considerable discrimination and they are presented in a standardized format" (Stubbs et al, 2000, p. 407).…”
mentioning
confidence: 99%